2000
DOI: 10.1097/00003226-200011000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Treatment of “Sterile” Midperipheral Corneal Infiltrates Associated with Soft Contact Lens Use

Abstract: The use of a topical corticosteroid alone may have a role in the treatment of presumed sterile midperipheral corneal infiltrates associated with SCLs when strict guidelines are followed. Such therapy suggests that the infiltrates are not the result of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 9 publications
0
10
0
3
Order By: Relevance
“…17 The event is noninfectious and resolves rapidly without the need for medical intervention. 23,24 However the signs and symptoms of this case rapidly worsened after lenses were removed, and diagnosis was revised the next day and appropriate therapy instituted. In the case study from Australia, signs rapidly worsened overnight after treatment with antibiotic ointment and patching.…”
Section: Discussionmentioning
confidence: 99%
“…17 The event is noninfectious and resolves rapidly without the need for medical intervention. 23,24 However the signs and symptoms of this case rapidly worsened after lenses were removed, and diagnosis was revised the next day and appropriate therapy instituted. In the case study from Australia, signs rapidly worsened overnight after treatment with antibiotic ointment and patching.…”
Section: Discussionmentioning
confidence: 99%
“…11 Early topical steroid application may prevent opaque healing 12 and is useful for limiting the inflammatory response and destruction of the corneal stroma 13 and for regulation of epithelial proliferation over inflamed stroma. 14 The use of topical steroids to treat corneal ulcers remains controversial, 15 and there is still no consensus on how these drugs should be used and, indeed, on whether they should be used at all. Some workers prescribe topical steroids only after a several-day period of antibiotic treatment that would sterilize the abscess.…”
mentioning
confidence: 99%
“…On presentation, all subjects with infiltrates reported symptoms often seen in CIEs, the most common of which were pain and discomfort, photophobia, and injection. 15,16 In this study, infiltrate and symptom resolution were concurrent, and all symptoms were resolved by the end of the active CIE. Regarding injection associated with CIEs, Cook and Langham previously reported a decrease in vascularization and blood flow to thickened cornea after treatment of the infiltrative event, which may have been observed in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Baum and Dabezies observed that 20/20 visual acuity was reported after the resolution of sterile midperipheral corneal infiltrates. 16 Furthermore, McClintic et al 19 reported that visual acuity can continue resolution for 3 to 12 months after ulcer resolution due to ongoing scar improvement. Hence, it is necessary for regular follow-up visits to be scheduled after severe infiltrate resolution and scar formation to monitor the restoration of visual acuity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation